Metodologias adaptadas para o ensino de Física para alunos autistas no Ensino Superior - BARBOSA, Milena Pinheiro (2023)
This work aims to present methodologies adapted to teach Physics content to Autistic students in Higher Education attended by the Accessibility Coordination of the Superintendence of Student Assistance (CoAcess / SAEST / UFPA). Five students with Autism Spectrum Disorder (ASD) regularly enrolled in undergraduate courses participated in the research: Biotechnology (2), Natural Sciences (1), Computer Science (1) and Physics Bachelor (1), who had in their curricular components the contents of General Physics. The research took place from 03/2019 to 12/2019, and the adapted methodologies and resources were: Concept Maps, Experimental Classes, Alternative Communication (Concept Cards), Adapted Games (Board and Quiz), Manga Magazines on Physics and Software of Simulations (Phet Simulations and Physics at School) based on 3 Pedagogical Moments (3PM). The monitoring experience with Autistic students made it possible to: (1) experience an inclusive practice that contributes to professional training, ensuring accessibility for these students, (2) observe the evolution of students from the adapted methodologies used during the monitoring activities, (3) to promote the relationship and application of theoretical and practical knowledge in the academic context, (4) to contribute to professional autonomy and (5) to stimulate social interaction and the creation of trust bonds between monitor, Autistic students and their family. This experience was considered significant for Autistic students, as it obeys what is proposed in Art. 27 of the Brazilian Inclusion Law (2015), in which education as a right of the Person with Disabilities (PwD) is ensured, as well as, access and stay in an inclusive educational system at all levels.